A Scientometric Analysis of Research Productivity in Surgery from Arab countries (2001-2021): Research Productivity in Surgery from Arab countries - Imran, Muhammad; Malik , Ahmad Azam (Pakistan Journal of Health Sciences, 2023)
Several surgical procedures are being performed on daily basis globally along with continuously expanding research in all surgery fields. Objective: To assess the surgery related research trends and performance in Arab countries using bibliometric indicators. Methods: In this descriptive bibliometric study, data were extracted from the Web of Science (WoS). All surgery related English language articles, from 2001 to 2021 from Arab countries were analyzed in R-Bibliometric package. Results: There were 10,269 articles in English language, with 158 authors’ countries. There was increase in publications each year with escalating trend from 2017 onwards. Al-Qattan MM was the leading author with >200 publications and >2000 total citations (TC)), while the highest h-index was demonstrated by Alio 25. Egypt USA, and Saudi Arabia were leading in production and TC. Cairo University (Egypt) and King Saud University (Saudi Arabia) were the leading affiliations. International Journal of Surgery Case Reports was the leading sources. Case report, bariatric surgery, surgery, laparoscopy and sleeve gastrectomy were the most frequently used keywords. Conclusions: This study showed increasing publications over time with more productivity since 2017. The magnitude and increasing trend of obesity and bariatric surgery-research was observed. Egypt and Saudi Arabia were leading contributors, which signifies the need of more efforts from other Arab countries. More collaboration among Arab researchers, increase in funding sources, efforts toward high impact research in the field of surgery, and support for less resourceful countries are warranted in future